2006
DOI: 10.1111/j.1475-3588.2005.00386.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Waiting List Initiative in a Child and Adolescent Mental Health Service

Abstract: Background: The aim of the study was to evaluate Initial Assessment (IA), a new system for managing referrals. The system is designed to: reduce waiting times, reduce 'did not attend' (DNA) rates, and improve multidisciplinary team working and team morale, compared to the existing referral procedure. Method: A comparison was made between a child mental health service using IA and a second centre using the existing system over a 6-month period, based on administrative records, a child functioning measure, staff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 10 publications
1
24
0
1
Order By: Relevance
“…Implementing flexible appointment hours to improve treatment access and attendance in child mental health treatment is essential. Pre-waitlist strategies (e.g., centralized intake process, triage incorporated into the intake process for prioritization of cases by clinical severity) are among the strategies used by agencies and found to demonstrate significant reductions in wait times and missed appointments (Clemente, McGrath, Stevenson, & Barnes, 2006; Williams, Latta, & Conversano, 2008). Other strategies may include providing immediate intervention services during assessment and prior to treatment, weekly monitoring of children and families on the waitlist, collaboration with other providers and agencies, and utilization of clinical pathways (Ingoldsby, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Implementing flexible appointment hours to improve treatment access and attendance in child mental health treatment is essential. Pre-waitlist strategies (e.g., centralized intake process, triage incorporated into the intake process for prioritization of cases by clinical severity) are among the strategies used by agencies and found to demonstrate significant reductions in wait times and missed appointments (Clemente, McGrath, Stevenson, & Barnes, 2006; Williams, Latta, & Conversano, 2008). Other strategies may include providing immediate intervention services during assessment and prior to treatment, weekly monitoring of children and families on the waitlist, collaboration with other providers and agencies, and utilization of clinical pathways (Ingoldsby, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…12 Changes in intake procedures appear to have positively influenced waiting for mental health services. 10,13,14 Adapting services to brief counselling sessions 15 or moving to consultative models of care may also improve wait times. 16 New models of service are a pragmatic alternative to an increase in funding.…”
mentioning
confidence: 99%
“…Those studies aimed at child populations include Clemente and colleagues’ () findings from the evaluation of a system designed to manage referrals to London‐based CAMHS services and reduce DNA rates. The authors found that the new system was associated with a significantly shorter average waiting time for the first appointment (nine weeks) and a lower DNA rate.…”
Section: Resultsmentioning
confidence: 99%